Biological activity and chemical composition of the essential oil from the fruits of Ferula halophila Peşmen - Kürkçüoğlu, Mine; İşcan, Gökalp; Tosun, Fatma; Miski, Mahmut (Istanbul Medipol University, 2023)
The hydrodistilled essential oils of the dried fruits of F. halophila Peşmen, an endemic species growing near Salt Lake in Central Anatolia, were analyzed by GC and GC-MS systems; 27 and 24 compounds representing 92.1% and 79.8% of the essential oils were characterized, respectively. The main component of the essential oils was identified as ?-phellandrene. The antibacterial and anticandidal effects of the essential oils were determined by using partly modified CLSI methods M7-A7 and M27-A2, respectively. The essential oils from two specimens showed weak to moderate inhibitory effects on the tested pathogenic bacteria (MIC, 125-2000 µg/ mL) and Candida panels (MIC, 156-1250 µg/mL).
Keywords: Antibacterial; Anticandidal; Essential Oil; Ferula Halophila